Older Baby Boomers Seeking Collegiate Degrees: Developmental Influences on Educational and Vocational Aspirations - Jane L. Schaefer (Adult Education Research Conference, 2009)
This paper summarizes findings from a phenomenological study designed to explore the experiences of degree-seeking, adult learners – specifically, Older Baby Boomers (OBB) born between 1946 and 1958. Findings seek to understand how adult development—psychosocial, cognitive, and spiritual dimensions—influences older adult students’ future aspirations, both career and retirement, and their transformational learning experiences within the context of higher education.